Molecular Docking Study of Novel Nitrofuran Derivatives As Urinary Tract Anti Infectives - Kolageri, Shivanand; Kamble, Siddaling; S, Viswanath; G, Meganathan; Alom, Khursid; S, Rajasekaran (Asian Journal of Pharmaceutical Research and Development, 2022)
Modern drug design commonly uses molecular docking to understand drug-receptor interaction. For docking tests against 1YLU, an E. coli nitro-reductase, substituted furan derivatives were used in the current work. The study's primary goal is to dock the chosen nitrofuran derivatives onto the protein and compare the results to those of nitrofurantoin as a standard drug. PyRx and the discovery studio visualizer (DSV) application were used to carry out the molecular docking analysis, and E. coli nitro-reductase (1YLU) was retrieved from the protein data bank (PDB) website. All seven of the nitrofuran compounds docking scores were discovered to range between -5.9 and -8.8 Kcal/mol. Compound 2a received the highest binding score, with a score of -8.80 Kcal/mol.At the protein active site, compound 2a interacts with amino acids such as glutamic acid (GLU 165), arginine (ARG 10 & 207), serine (SER 39 & 12), glutamine (GLN 142), and lysine (LYS205).Numerous nitrofuran substituted compounds have been identified for the activity and the nitrofuran derivatives have been discovered to exhibit urinary tract anti-infective activities.